The role of social media in the process of shaping the "body cult" amongyoung women - Iwanicka, Aleksandra; Soroka, Ewelina (Current Problems of Psychiatry, 2020)
Introduction. The purpose of this article is to analyse the phenomenon of "body cult" as well as psychological and social factors conditioning its occurrence among young women. Particular attention was paid to the role of social media and an attempt was made to indicate possible preventive measures to promote health-popularising behaviour towards the body among high school students.Materials and methods. On the basis of the review of the available literature, developmental conditions of the adolescence period and research results on the subject were presented.Results. The paper presents the role of social media in the context of shaping behaviours related to "body cult".Conclusions. The content presented on blogs and social networks put pressure on young women to cultivate the physical characteristics of a person. In this perspective, excessive focus on striving for the perfect figure can lead to the development of anti-health behaviour. Further research is definitely needed.